The Influence of Facilities and Infrastructure on Increasing Student Learning Motivation in the MPI IAIN Curup Study Program - Syaiful Bahri; Murni Yanto; Muhammad Ajmal; Yasir Riady; Abdul Shahib (CV Media Inti Teknologi, 2025)
Background of Study: Particularly at higher education institutions, the provision of sufficient infrastructure and learning facilities is crucial for fostering student enthusiasm and academic achievement. Many study programs still have restrictions in this regard, however.Aims and Scope of Paper: This study aims to determine what facilities and infrastructure are needed in the MPI Study Program to support the learning process and whether these facilities and infrastructure affect the learning motivation of MPI study program students at IAIN Curup.Method: This research is a type of correlation study with two independent and dependent variables. The population of this study consisted of 94 students, with 25 eighth-semester students serving as a test sample for the questionnaire, while 69 second, fourth, and sixth-semester students comprised the research sample. Data collection techniques included questionnaires and unstructured interviews, using instruments with a modified Likert scale. Simple linear regression was used as part of data analysis methods.Result: The findings demonstrated that the infrastructure and learning facilities had a favorable and noteworthy impact on the students' motivation to learn in the MPI IAIN Curup study program, expressed by the regression equation Ŷ = 1,846 + 1,220 Χ. The strength of the influence or causality relationship is indicated by the beta coefficient of 0.955.Conclusion: Given the significant positive influence of learning facilities and infrastructure on learning motivation, there is a need to enhance the MPI IAIN Curup study program's infrastructure and learning facilities' accessibility and use.